1991
DOI: 10.1080/18811248.1991.9731383
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Failure and Fracture Mechanics of Graphites for High Temperature Engineering Testing Reactor

Abstract: The effect of stress ratio, irradiation, oxidation, specimen volume and cumulative damage on fatigue behavior and fracture toughness were examined for HTTR (High Temperature Engineering Test Reactor) component materials, IG-110 and PGX graphites, and the following conclusions were derived: (1) The fatigue strength of IG-11 graphite, which is non-purified IG-110 graphite, decrease with decreasing stress ratio and crack extension speed was enhanced mainly by the increment of cyclic peak load. (2) The increment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…16 A few studies of fracture from notches have been carried out under mode II 26,27 and mixed mode 28,29 loading conditions, and the notch sensitivity of graphite has also been investigated using a strain energy density approach. 28,29 Some early studies 3,[30][31][32][33] have reported fatigue crack growth and fatigue lives of nuclear graphite. However, these offer limited insight into the material behaviour during crack growth under cyclic loading conditions, mainly due to the limitations in the methods of studies in the past.…”
Section: Introduction †mentioning
confidence: 99%
“…16 A few studies of fracture from notches have been carried out under mode II 26,27 and mixed mode 28,29 loading conditions, and the notch sensitivity of graphite has also been investigated using a strain energy density approach. 28,29 Some early studies 3,[30][31][32][33] have reported fatigue crack growth and fatigue lives of nuclear graphite. However, these offer limited insight into the material behaviour during crack growth under cyclic loading conditions, mainly due to the limitations in the methods of studies in the past.…”
Section: Introduction †mentioning
confidence: 99%